Escalation Of Divorce By Wife At The Class 1a Religious Court Of Palu In The Perspective Of Feminist Legal Theory - Fira Farisda; Nasaruddin Nasaruddin; Suhari Hanafi (UNIVERSITAS PAKUAN, 2026)
Divorce by wife has emerged as a dominant structural phenomenon in Indonesia’s religious courts, reflecting shifting power dynamics and increasing legal awareness among women. This research examines the escalation of cerai gugat at the Class 1A Religious Court of Palu, focusing on its causal factors and socio-legal implications through the lens of feminist legal theory. Using a qualitative case study approach, data were gathered from semi-structured interviews with judges, court officials, and litigants, alongside a thematic analysis of court decisions. Findings indicate that cerai gugat accounts for approximately 70% of divorce cases in Palu, driven primarily by chronic gender imbalances, economic instability, and domestic violence. Despite the high volume of cases filed by women, the transition from legal object to active subject has not fully translated into substantive justice. Post-divorce, women remain trapped in cycles of social stigma and economic vulnerability due to inconsistent ex officio maintenance orders and weak execution mechanisms. The study concludes that the religious judicial system remains largely formalistic, necessitating a shift toward gender-responsive practices and the integration of Islamic feminist principles to ensure the effective protection of women’s rights.